Motivations for Customer Engagement due to Consumer Innovativeness - Paweł BARTKOWIAK; Szymon MICHALAK (Communications of International Proceedings, 2020)
The main goal of the paper is to identify the differences in customer engagement motivation due to the level of consumer innovativeness and advance knowledge regarding motives of consumer engagement. The research part of the paper presents the characteristics of segments based on innovative predispositions of the inhabitants of the Poznań agglomeration, identification of statistically significant differences between these segments regarding motivational factors, definition of criteria for segmentation of the research population in terms of customer engagement motivation and the relationship between those segments and segments based on innovative predispositions. The study was conducted by means of direct interviews using an interview questionnaire, on a sample of 795 inhabitants of the Poznań agglomeration and its results indicate that material motivation for engagement in value co-creation is far more important than intangible motivation.
Keywords: Consumer innovativeness; customer engagement (CE); consumer behaviour; value co-creation; motivation; consumer segmentation.